To subjugate a vampire: part 1 - Ramble, C; Tsewang, K (University of Oxford, 2021)
The ritual presented here was recorded on video and subsequently edited using Final Cut Pro. The footage can be viewed with any software that plays .mov files. Further information about the ritual and the project within which the video was made can be found on: http://kalpa-bon.com/